Unveiling the role of post-translational modifications in bone metabolism: implications for osteoporosis - Suleiman Kolawole Yusuf; Abubakar Danmaigoro; Onwuama Kenechukwu Tobechukwu; Samuel Odo Uko; Sadudeen Adetayo Amid; Okediran Babatunde Samuel; Alhaji Zubair Jaji (Medicine in Novel Technology and Devices)
Bone metabolism is a highly dynamic process regulated by osteoblasts, osteoclasts, and osteocytes, ensuring skeletal integrity through continuous remodeling. Disruptions in this balance contribute to osteoporosis, a debilitating condition characterized by reduced bone mass and increased fracture risk. Emerging research highlights the pivotal role of post-translational modifications (PTMs) in regulating bone cell activity, influencing protein stability, function, and signaling pathways. Key PTMs, including phosphorylation, glycosylation, acetylation, ubiquitination, and SUMOylation, govern osteoblast differentiation, osteoclast activity, and extracellular matrix organization. Dysregulation of these modifications has been linked to osteoporosis pathogenesis, making them promising therapeutic targets. RUNX2, a master osteogenic transcription factor, is extensively regulated by PTMs, affecting its activity in skeletal development. Similarly, extracellular matrix proteins and osteocyte-derived factors, such as sclerostin and fibroblast growth factor 23, undergo PTMs that influence bone homeostasis. Advances in proteomics and molecular biology have facilitated the identification of PTM-mediated mechanisms, paving the way for targeted therapies, including kinase inhibitors, histone deacetylase modulators, and ubiquitination regulators. This review explores the mechanistic contributions of PTMs in bone metabolism, their dysregulation in osteoporosis, and potential therapeutic interventions, offering insights into novel strategies for bone health preservation and osteoporosis treatment.